Perencanaan Strategis Sistem Informasi Sumber Daya Manusia Pada STMIK Banjarbaru - Kiki Olivia - STMIK Banjarbaru (Indonesian Journal of Networking and Security (IJNS), 2016)
Abstract - STMIK Banjarbaru have a strategic plan , The to do is create a strategic plan in STMIK Banjarbaru Information Systems , focusing attention on the part of human resources using the value chain approach (value chain ). The study was conducted with the objective to build your strategic planning of human resources information system STMIK Banjarbaru to create a competitive advantage in realizing the vision , mission and goals of the organization. Given this research will facilitate the management of Human Resources ( HR) in STMIK Banjarbaru to increase its competitive advantage by using strategic planning of human resources information system .Keywords : strategic planning of information systems , human resources , value chain , five force porter , Mc Farlan . Abstract - STMIK Banjarbaru memiliki rencana strategis, Adapun yang dilakukan adalah membuat rancangan strategis Sistem Informasi di STMIK Banjarbaru, dengan fokus perhatian pada bagian Sumber daya manusia menggunakan pendekatan rantai nilai (value chain)Penelitian dilakukan dengan tujuan Membuat perencanaan strategis sistem informasi sumber daya manusia STMIK Banjarbaru untuk menciptakan keunggulan bersaing dalam mewujudkan visi, misi dan tujuan organisasi,.Dengan adanya penelitian ini akan memudahkan dalam pengelolaan Sumber Daya Manusia (SDM) pada STMIK Banjarbaru untuk meningkatkan keunggulan kompetitifnya dengan menggunakan perencanaan strategis system informasi Sumber Daya Manusia.Kata kunci : Perencanan strategis sistem informasi, Sumber Daya Manusia, Analisa value chain, Five Force Porter